EUROPEAN BORDER SECURITY: RETHINKING THE CONCEPT OF OPEN BORDERS - Adnan Mahmutovic; Abdulaziz Alhamoudi (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2023)
This paper examines the concept of integrated border management in the context of the European Union. Integrated border management refers to a collaborative approach among all entities involved in border activities, aimed at mitigating potential adverse consequences arising from the removal of internal border controls. The task of achieving a harmonious equilibrium between facilitating unrestricted movement across borders and ensuring robust external border protection poses noteworthy difficulties and consequences. This research investigates the progression of integrated border management within the European Union and its impact subsequent to the Tampere meeting in 2006. This study examines the fundamental attributes of the European integrated border management model and evaluates its efficacy in managing irregular migration and security threats, while simultaneously facilitating unhindered mobility within the European Union. The study also examines the promotion and implementation of the key principles of integrated border management among member states of the European Union in order to strengthen external border control and maintain stability within the Schengen Area. Furthermore, this study evaluates the significance of risk analysis in facilitating the implementation of European integrated border management. It also examines how risk analysis can be utilized to enhance the efficiency of border assets and effectively address risks of different magnitudes. Abstrak: Artikel ini mengkaji konsep pengelolaan perbatasan terpadu dalam perpektif Uni Eropa. Pengelolaan perbatasan terpadu mengacu pada pendekatan kolaboratif di antara semua pihak yang terlibat dalam pengelolaan perbatasan, bertujuan untuk memitigasi potensi dampak buruk yang timbul dari penghapusan kontrol internal perbatasan. Hal ini bertujuan untuk mencapai keseimbangan harmonis antara memfasilitasi pergerakan tanpa batas, dalam melintasi perbatasan serta memastikan perlindungan perbatasan eksternal yang kuat, dari timbulnya kesulitan dan konsekuensi yang patut diperhatikan secara bersama. Penelitian dalam artikel ini menginvestigasi tindak lanjut manajemen perbatasan terpadu dalam Uni Eropa serta akibat yang ditimbulkan terhadap pertemuan Tampere tahun 2006. Kajian artikel ini menguji atribut dasar tentang model manajemen perbatasan terpadu di Eropa, serta mengevaluasi, dan mengevaluasi keberhasilannya dalam mengelola migrasi tidak teratur dan ancaman keamanan, sekaligus memfasilitasi mobilitas tanpa hambatan di dalam Uni Eropa. Artikel ini juga mengkaji penerapan prinsip-prinsip utama pengelolaan perbatasan terpadu di antara negara-negara anggota Uni Eropa dalam memperkuat kontrol perbatasan eksternal dan menjaga stabilitas di Wilayah Schengen. Lebih lanjut, penelitian ini mengevaluasi pentingnya analisis risiko dalam memfasilitasi penerapan pengelolaan perbatasan terpadu Eropa. Disamping itu juga mengkaji bagaimana analisis risiko dapat digunakan untuk meningkatkan efisiensi aset perbatasan secara efektif, khususnya dalam mengatasi risiko dengan besaran yang berbeda-beda. Kata Kunci: Uni Eropa, Manajemen Perbatasan Terpadu Eropa, Migrasi, Analisis Risiko